Identification of a surface antigen on Theileria parva sporozoites by monoclonal antibody. - Dobbelaere, D A (1985)
A mouse monoclonal antibody (mAbD1) that neutralizes sporozoites of different stocks of the protozoan parasite Theileria parva has been used to localize and identify a sporozoite antigen. Protein A-colloidal gold was used to localize bound mAbD1 in immunoelectron microscopic studies. mAbD1 bound to sporozoite antigen, which was evenly spread over the surface of all sporozoites. Immune complexes were obtained by incubation of sporozoite suspensions with mAbD1 followed by Zwittergent 3-14 extraction and precipitation with protein A-Sepharose. One- and two-dimensional NaDodSO4/polyacrylamide gel electrophoretic analyses were performed on these complexes, and a major protein with a molecular size of 68 kDa was identified. Other related components of 52 kDa, 47 kDa, and 28 kDa were also detected. Since antibody to this antigen(s) neutralizes T. parva sporozoites from different stocks, the results could be of relevance to the development of a broad spectrum vaccine against the cattle disease East Coast fever, which is caused by T. parva.